2004
DOI: 10.1614/wt-03-164r1
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Kochia (Kochia scoparia) Management with Herbicides in Small Grains

Abstract: Uncontrolled kochia plants that regrow after small-grain harvest can produce substantial numbers of seeds. An average of 4,100 seeds per plant were produced between harvest (late July to mid August) and the first killing frost (late September) at three locations in Montana. Field experiments were conducted to determine the optimal timing of postharvest herbicide applications to prevent kochia from producing viable seeds. Herbicide treatments were applied at three timings from late August to mid September. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 15 publications
(18 reference statements)
3
25
0
Order By: Relevance
“…Although kochia germinates and emerges mainly in early spring, additional flushes can occur throughout the growing season (MAFRI 2006). Kochia may emerge after postemergence herbicide application, resulting in substantial uncontrolled populations (Mickelson et al 2004). In southern Manitoba, Schwinghamer and Van Acker (2008) observed kochia emergence throughout the growing season, albeit in small numbers after the initial flush in early spring.…”
Section: MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Although kochia germinates and emerges mainly in early spring, additional flushes can occur throughout the growing season (MAFRI 2006). Kochia may emerge after postemergence herbicide application, resulting in substantial uncontrolled populations (Mickelson et al 2004). In southern Manitoba, Schwinghamer and Van Acker (2008) observed kochia emergence throughout the growing season, albeit in small numbers after the initial flush in early spring.…”
Section: MMmentioning
confidence: 99%
“…Additionally, postemergence herbicides or mixtures such as atrazine, dicamba plus 2,4-D, or bromoxynil plus MCPA control kochia in corn (Blackshaw 1990;Saskatchewan Agriculture and Food 2008). In the northern Great Plains of the USA, glyphosate or paraquat applied post-harvest effectively reduced seed production from kochia plants that regrew after wheat or barley harvest (Mickelson et al 2004).…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…However, with the increased use of glyphosate, fields in Iowa, Illinois, and Missouri began reporting GR weed species (Culpepper, 2006;Owen, 2002;Rosenbaum & Bradley, 2013). Additionally, glyphosate and ALS-inhibiting herbicides are predominant chemistries used to control kochia in chemical-fallow, pre-plant burndown, and post-harvest in wheat (Donald & Prato, 1991;Lloyd et al, 2011;Mickelson et al, 2004;Kumar et al, 2014;Kumar & Jha, 2015a, 2015b. In a recent research Kumar et al (2015) reported the underlying mechanisms of glyphosate and ALS resistance in kochia accessions from Montana.…”
Section: Introductionmentioning
confidence: 99%
“…In each year at each location, tumble pigweed control by carfentrazone plus dicamba or 2,4-D treatments was less than all other treatments except bromoxynil (30 to 89%). Mickelson et al (2004) also found inconsistent kochia (Kochia scoparia L.) control by bromoxynil, carfentrazone, or 2,4-D under summer-fallow drought stress conditions.…”
mentioning
confidence: 95%